BabaoDan attenuates high-fat diet-induced non-alcoholic fatty liver disease via activation of AMPK signaling - Sheng, Dandan; Zhao, Shanmin; Gao, Lu; Zheng, Huifei; Liu, Wenting; Hou, Jing; Jin, Yuxiang; Ye, Fei; Zhao, Qiudong; Li, Rong; Zhao, Naping; Zhang, Li; et al. (Cell & bioscience, 2019)
Babaodan (BBD), a traditional Chinese medicine, has been shown to have protective effects during liver injury and ameliorate liver disease progression, but little is known about its effect on non-alcoholic fatty liver disease (NAFLD). The aim of this study was to investigate the effects of BBD on obesity-induced NAFLD. C57BL/6 J mice were fed with normal diet, high fat diet (HFD) or HFD + BBD for 8 weeks. Weights of all mice were recorded every 3 days. At the end of the experiments, the level of livers, kidneys and adipose tissues of each animal was weighed. Blood serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total cholesterol (TC), triglyceride (TG), high density lipoprotein cholesterol (HDL-C) cholesterol, low density lipoprotein cholesterol (LDL-C), glucose and leptin were detected with appropriate test kits. Haematoxylin-eosin (HE), Masson trichrome and Oil Red O staining of the liver were performed. We applied immunohistochemical analysis to investigate the expression of TNF-α, IL-6 and leptin in liver tissue. The expression of genes related lipid anabolism (SREBP1-c, ACC, SCD-1, LXRα and CD36) and ß-oxidation (CPT-1 and PPARα) in liver and adipose tissues was determined by RT-PCR. The expression of AMPK and p-AMPK was determined by western blot analysis. We found the weight of bodies and tissues (retroperitoneal fat pads, kidneys and livers) of mice fed with HFD + BBD were significantly lower than that of HFD-fed mice. And liver injury induced by HFD was relieved in mice treated with BBD, accompanied with significant reduction were observed in serum ALT/AST activities and alleviated pathological damage. The levels of glucose, TG, TC, HDL-C and LDL-C in the liver or serum were significantly decreased on HFD + BBD group compared with HFD group. Furthermore, BBD treatment reduced the level of TNF-α and IL-6 induced by HFD. The level of leptin in the liver and serum were reduced in mice fed with HFD + BBD than that of HFD-fed mice. Several lipid synthesis genes (SREBP1-c, ACC, SCD-1, LXRα and CD36) were down-regulated and that of ß-oxidation (CPT-1 and PPARα) up-regulated in HFD + BBD group compared with HFD group. In addition, BBD increased the expression of p-AMPK compared with untreated HFD group, which suggested BBD improved the activation of AMPK pathway. In summary, our results indicate that BBD has potential applications in the prevention and treatment of NAFLD, which may be closely related to its effect on lipid metabolism via activation of AMPK signaling.